THE STUDY OF WATER RESISTANCE OF THE SOIL-CEMENT - Zocenko, M. L.; Nalyvajko, O. I.; Lartseva, I. I.; Panko, O. M. (Science and Transport Progress, 2010)
The study of watertightness of the soil cement by speed-up method for air permeability determination by means of the ВВ-2 device («Аgamа» type) is presented in this article. The coefficient of softening is also determined.